The Recovery on Trauma of the Main Character in See You on Venus Movie - Novitasari, Ulfa (EDUJ : English Education Journal, 2024)
Trauma is a condition that arises as a result of a scary experience or event that happened to someone, such as natural disasters, physical violence, sexual harassment, and traffic accident. The response caused by trauma is have suicidal thought and depression, which affects a person's mentality due to the traumatic event they experienced. The purpose of this study is to know the causes and effects of trauma and how to recovery from trauma diseases. In this study, the writer used a descriptive-qualitative method. The writer watches the movie and identifies the data, then analysis all trauma in See You on Venus movie. In this study, the writer found that in the main character of See You on Venus movie, caused trauma by traffic accident and lost his close friend. Because that accident, he gets pressure and have suicidal thought to end his life. The effort of main character to get out from trauma condition is because partner sharing and travelling to new place.